2013
DOI: 10.4103/2321-3868.123072
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and cardiac dysfunction during sepsis, muscular dystrophy, and myocarditis

Abstract: Inflammation plays an important role in cardiac dysfunction under different situations. Acute systemic inflammation occurring in patients with severe burns, trauma, and inflammatory diseases causes cardiac dysfunction, which is one of the leading causes of mortality in these patients. Acute sepsis decreases cardiac contractility and impairs myocardial compliance. Chronic inflammation such as that occurring in Duchenne muscular dystropshy and myocarditis may cause adverse cardiac remodeling including myocyte hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 119 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…Potential mechanisms explaining the increased NT-proBNP levels during sepsis are still debated. The most accepted hypothesis is that cardiac insufficiency during sepsis is caused by the impact of the pro-inflammatory response and ventricular overload during aggressive fluid resuscitation therapy [15, 37]. Current literature argues that sepsis-induced cardiac dysfunction is a reversible condition driven by functional rather than structural changes, with a complete resolution within 7–10 days in survivors [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms explaining the increased NT-proBNP levels during sepsis are still debated. The most accepted hypothesis is that cardiac insufficiency during sepsis is caused by the impact of the pro-inflammatory response and ventricular overload during aggressive fluid resuscitation therapy [15, 37]. Current literature argues that sepsis-induced cardiac dysfunction is a reversible condition driven by functional rather than structural changes, with a complete resolution within 7–10 days in survivors [24].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, patients suffering from sepsis show signs of cardiac insufficiency [14]. Indeed, the destructive systemic inflammatory response and intensive resuscitation occurring during sepsis result in widespread organ overload and damage including myocardial injury [15]. Additionally, experimental studies have demonstrated that endotoxins and cytokines directly increase gene expression of BNP, explaining the higher levels of this biomarker during sepsis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Methylthioadenosine is a sepsis biomarker that is involved in the inflammatory response and is related to high rates of fever-induced host cell death ( 19 ). Several previous studies have shown that sepsis is associated with the inflammatory response in the heart ( 8 , 20 , 21 ), but the detailed molecular mechanism remains unclear. The Wnt and inflammatory response pathways were associated with T cell-specific transcription factor (TCF)/lymphoid enhancer-binding factor (LEF) ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial depression is seen in approximately 50% of patients with severe sepsis, with high mortality rate as high as 70–90% 1 . A number of mechanisms have been proposed to be involved in sepsis induced myocardial dysfunction (SIMD), including bacterial toxins induced excessive production of pro-inflammatory cytokines, complement activation 2 , dysregulation of intracellular calcium transporters 3 , and mitochondrial dysfunction 4 .…”
Section: Introductionmentioning
confidence: 99%